Synthesis of Bio-additive for Low Sulphur Diesel: Transesterification of Soybean Oil and Ethylene Glycol using K2CO3 Catalyst - Rhiby Ainur Basit Hariyanto; R. Arizal Firmansyah; R. Y. Perry Burhan; Yulfi Zetra (Automotive Experiences, 2021)
The desulphurization process of diesel fuel is carried out to reduce the amount of SO2 emissions that can cause acid rain. However, the desulphurization process in diesel fuel not only removes the sulfur compounds but polyaromatic and polar compounds are also eliminated during this process. The loss of these two compounds can reduce the lubricity properties of diesel fuel. Therefore, it is necessary to add an additive compound that can increase the lubricity properties. In this research, 2-hydroxyethyl ester (HEE) was synthesized as an additive to increase the lubricity of diesel fuel. This compound was synthesized through the transesterification reaction of soybean oil and ethylene glycol with K2CO3 as the base catalyst. The composition of the synthesized additives was analyzed using the Gas Chromatography-Mass Spectrometry (GC-MS). Based on the results of GC-MS spectrum analysis, it is known that the 2-hydroxyethyl ester compound has been formed with a yield of 66.5% (relative to the area of the chromatogram peak). The HEE compound obtained is a mixture of 2 hydroxyethyl palmitate, 2 hydroxyethyl linoleate, 2 hydroxyethyl stearate, 2 hydroxyethyl arachidonate, 2 hydroxyethyl nervate, and 2 hydroxyethyl behenate.